The energy spectra of the graphene-based quasi-periodic superlattice - Korol, Anatoliy; Sokolenko, Anatoly; Sokolenko, Igor (My University, 2018)
The spectra of the Dirac quasielectrons transmission through the Fibonacci quasi-periodical superlattice (SL) are calculated and analyzed in the continuum model with the help of the transfer matrix method. The one-dimensional SL based on a monolayer graphene modulated by the Fermi velocity barriers is studied. A new quasi-periodical factor is proposed to be considered.
Keywords: quasielectrons Dirac; transmission spectra; квазіелектрони Дірака; спектри трансмісії; кафедра фізики та професійної безпеки; кафедра мехатроніки та пакувальної техніки